PNPB CREDIT MANAGEMENT AT THE MINISTRY OF ESDM - Syarief Gerald Prasetya (The Accounting Journal of Binaniaga, 2016)
State Non-taxable Revenue (PNBP) from the energy and mineral sources (ESDM) sectors, particularly at Oil and earth gas(Migas) sector, coal and mineral sector, are very significant revenue of the state which is State Non-taxable Revenue described on the National budget and revenue(APBN). Actually there are still a lot of BUMN, BUMD, private companies which have not paid yet their PNBP to the Ministry of ESDM.. This research aims to recognize empirically the system of PNBP management within the Ministry of ESDM. This research has applied an analytical descriptive method which is a method to provide an actual condition regarding the credit management. The State revenue refers to PNBP credit has still been beyond the expectation due to a slow process of PNBP credit administration as well as the organization management which has not been running well. An effort to speed up the process should have to be applied refers to the efficiency of the related sources consumed such as time, cost and manpower. An effort to develop the effectiveness of State credit administration should have to be applied by improving the organization performance to maximize the result of the State credit management.